The organ procurement costs of expanding deceased donor organ acceptance criteria: Evidence from a cost function model. Issue 11 (8th May 2021) - Cheng, Xingxing S.; Held, Philip J.; Dor, Avi; Bragg‐Gresham, Jennifer L.; Tan, Jane C.; Scandling, John D.; Chertow, Glenn M.; Roberts, John P.
Abstract : A potential solution to the deceased donor organ shortage is to expand donor acceptability criteria. The procurement cost implications of using nonstandard donors is unknown. Using 5 years of US organ procurement organization (OPO) data, we built a cost function model to make cost projections: the total cost was the dependent variable; production outputs, including the number of donors and organs procured, were the independent variables. In the model, procuring one kidney or procuring both kidneys from double/ en bloc transplantation from a single‐organ donor resulted in a marginal cost of 55 k (95% confidence interval [CI] 28 k, 99 k) per kidney, and procuring only the liver from a single‐organ donor results in a marginal cost of 41 k (95% CI 12 k, 69 k) per liver. Procuring two kidneys for two candidates from a donor lowered the marginal cost to 36 k (95% CI 22 k, 66 k) per kidney, and procuring two kidneys and a liver lowers the marginal cost to 24 k (95% CI 17 k, 45 k) per organ. Economies of scale were observed, where high OPO volume was correlated with lower costs. Despite higher cost per organ than for standard donors, kidney transplantation from nonstandard donors remained cost‐effective based on contemporary US data. Abstract : Procurement costs for nonstandard donors are higher than for standard donors, given the lower organ yield in nonstandard donors.